The Effect of Locus of Control, Leadership Style, and Organizational Culture on Employee Performance Through Organizational Commitment as an Intervening Variable - Romanza, Rafi; Elfiswandi, Elfiswandi; Very, Jhon (UPI YPTK Journal of Business and Economics, 2024)
The Effect of Locus of Control, Leadership Style, and Organizational Culture on Employee Performance through Organizational Commitment as an Intervening Variable at BKPSDMD Kerinci Regency focuses on the employees of the BKPSDMD Office in Kerinci Regency. This study uses a quantitative causal research design, with data collection conducted through questionnaires. The analysis technique applied is multiple linear regression, aided by the SmartPLS program. The sampling technique uses a saturated sample, analyzing responses from 70 participants. Based on the analysis results, it can be concluded that locus of control has a positive and significant effect on organizational commitment. Leadership style also has a positive and significant effect on organizational commitment. However, organizational culture does not affect organizational commitment. Locus of control has a positive and significant effect on employee performance, and leadership style similarly has a positive and significant effect on employee performance. Organizational culture, however, does not affect employee performance. Furthermore, organizational commitment does not affect employee performance and does not mediate the effect of locus of control on employee performance. However, organizational commitment mediates the effect of leadership style on employee performance and the effect of organizational culture on employee performance.